Galvanic Displaced Nickel-Silicon and Copper-Silicon Interfaces: A DFT Investigation. (5th January 2017) - Pedrazzetti, Lorenzo; Soltani, Peiman; Mezzi, Alessio; Kaciulis, Saulius; Nobili, Luca; Tommasini, Matteo Maria Saverio; Magagnin, Luca
Abstract : Metallization of semiconductors surfaces via galvanic displacement has proved its valor in all the microfabrication industry. Here is proposed a novel application of this technique as suitable route to deposit metal layers that serve as catalysts for graphene growth via chemical vapor deposition. Furthermore, a computational approach is described in order to understand and explain the behavior the two systems show at room temperature. Closing remarks are devoted to show the application of the cited process to micro structured polycrystalline silicon.